Prevention and Control of Blood Stream Infection Using the Balanced Scorecard Approach - Rinawati Rohsiswatmo; Sarah Rafika; Putri M.T Marsubrin (Acta Medica Indonesiana)
Aim: to obtain formulation of an effective and efficient strategy to overcome blood stream infection (BSI). Methods: operational research design with qualitative and quantitative approach. The study was divided into two stages. Stage I was an operational research with problem solving approach using qualitative and quantitative method. Stage II was performed using quantitative method, a form of an interventional study on strategy implementation, which was previously established in stage I. The effective and efficient strategy for the prevention and control of infection in neonatal unit Cipto Mangunkusumo (CM) Hospital was established using Balanced Scorecard (BSC) approach, which involved several related processes. Results: the BSC strategy was proven to be effective and efficient in substantially reducing BSI from 52.31o/oo to 1.36o/oo in neonates with birth weight (BW) 1000-1499 g (p=0.025), and from 29.96o/oo to 1.66o/oo in BW 1500-1999 g (p=0.05). Gram-negative bacteria still predominated as the main cause of BSI in CMH Neonatal Unit. So far, the sources of the microorganisms were thought to be from the environment of treatment unit (tap water filter and humidifying water in the incubator). Significant reduction was also found in neonatal mortality rate weighing 1000-1499 g at birth, length of stay, hospitalization costs, and improved customer satisfaction. Conclusion: effective and efficient infection prevention and control using BSC approach could significantly reduce the rate of BSI. This approach may be applied for adult patients in intensive care unit with a wide range of adjustment.